2023
DOI: 10.1111/apa.16938
|View full text |Cite
|
Sign up to set email alerts
|

Infants born to first‐time mothers with a refugee background faced an increased risk of regulatory problems

Maria Marti‐Castaner,
Camila Hvidtfeldt,
Sarah Fredsted Villadsen
et al.

Abstract: AimThis study investigated the association between mothers’ migration background and infant regulatory problems and analysed the mediating role of maternal mental health. We also explored whether the child's sex, parity and length of residence moderated the effect of a maternal migrant background.MethodsChild health surveillance data from the Danish home visiting programme was used. Community health nurses followed infants from birth to 12 months of age. The source population comprised 103,813 infants born bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…A Danish study by Marti‐Castaner et al 9 . found that a maternal refugee background increased the risk of infant regulatory problems, such as excessive crying and difficulties feeding and sleeping.…”
Section: Regulatory Problems Were Higher In Infants Born To Mothers W...mentioning
confidence: 99%
“…A Danish study by Marti‐Castaner et al 9 . found that a maternal refugee background increased the risk of infant regulatory problems, such as excessive crying and difficulties feeding and sleeping.…”
Section: Regulatory Problems Were Higher In Infants Born To Mothers W...mentioning
confidence: 99%
“…portrefugeefamilies.Theirlarge,population-basedstudyfoundan increased risk of regulatory problems in infants born to first-time mothers with a refugee background. 1 The authors collected information from community nurses on regulatory problems reported byparents,suchassleeping,feeding,eatingandexcessivecryingor fussiness.Theirresultsshowedthatinfantsborntorefugeemothers were more likely to have regulatory problems than those born to non-refugee immigrant mothers and infants from the majority Danishpopulation.…”
mentioning
confidence: 99%
“…In this issue of Acta Paediatrica , Marti Catstaner et al provide new and important knowledge that could help well‐baby clinics to support refugee families. Their large, population‐based study found an increased risk of regulatory problems in infants born to first‐time mothers with a refugee background 1 . The authors collected information from community nurses on regulatory problems reported by parents, such as sleeping, feeding, eating and excessive crying or fussiness.…”
mentioning
confidence: 99%
See 1 more Smart Citation